INTERAKSI BELAJAR MENGAJAR DALAM PEMBELAJARAN FISIKA DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INVESTIGASI KELOMPOK PADA SISWA KELAS X1 SMA NEGERI I TAMBANG KAMPAR - Mitri Irianti; Lisma Nurliza; M. Rahmad (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2007)
The purpose of this research was to describe teaching-learning interaction in teaching physics by applying cooperative teaching in terms of the type of group investigation by the first-year students at SMAN 1 Tambang Kampar. The research instrument used in this research was observation sheet. It was used by aspect observed based on cooperative teaching in terms of the type of group investigation. The model aims to motivate the student, to set the problem in the group, to report the result of group activities, and conclude the lesson. The technic of data collection was by observing teaching-learning interaction, which happened in each aspect observed every two minutes during the teaching process. The data analysis was by counting the percentage of teaching-learning interaction. The result of this research showed that the interaction of teaching-learning between teachers and students, students and teachers, students, and students happened to each step in teaching activity. The highest percentage of teaching-learning interaction was in the problem-solving of group activity. Hence, cooperative teaching in term of the type of group investigation is able to create teaching-learning interaction which various in teaching.